Planning Agricultural Research: A Sourcebook - Gijsbers, Govert; Janssen, Willem G.; Hambly Odame, Helen; Meijerink, Gerdien W. (CAB International, 2001)
Agricultural research is an investment in future production, productivity, and food security. But it is an uncertain business, because the investments required are large and the benefits are unknown and far away. Planning in agricultural research aims to guide the investments towards the most relevant outputs, in the most cost-effective manner. New approaches to planning are emerging that emphasize the use of plans to identify strategic issues and to help organizations adjust to rapidly changing conditions in the external environment. These ideas are important for agricultural research organizations, which must balance the need to adjust to changing circumstances with the long-term nature of agricultural research. The book provides a variety of perspectives on agricultural research planning, grouped into four sections dealing with the context of planning, planning content, planning processes, and planning tools. A glossary provides an overview of concepts and definitions.